2014
DOI: 10.3189/2014aog68a028
|View full text |Cite
|
Sign up to set email alerts
|

Drill fluid selection for the SUBGLACIOR probe: a review of silicone oil as a drill fluid

Abstract: As part of the ICE&LASER/SUBGLACIOR projects, an innovative probe called SUB-GLACIOR is developed with the aim of perforating the ice sheet down to depths of 3500 m in a single season and continuously measuring in situ the isotopic composition of the meltwater and the methane concentration in trapped gases. Ice chips generated by the electromechanical drilling will be removed from the borehole by circulating a drill fluid. The selection of this drill fluid is important as it will have a major impact on the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In addition, this fluid is environmentally friendly. Our tests in the laboratory have shown that it does not interfere with the OF-CEAS spectrum in case of contamination of the water (Triest and others, 2014). Furthermore, our tests in a cold room at −10°C, where we dropped ice chips into 3 L of silicone oil and let the mixture sit for >6 weeks, showed no cluster formation.…”
Section: The Subglacior Probe Conceptmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, this fluid is environmentally friendly. Our tests in the laboratory have shown that it does not interfere with the OF-CEAS spectrum in case of contamination of the water (Triest and others, 2014). Furthermore, our tests in a cold room at −10°C, where we dropped ice chips into 3 L of silicone oil and let the mixture sit for >6 weeks, showed no cluster formation.…”
Section: The Subglacior Probe Conceptmentioning
confidence: 84%
“…After evaluating several types of fluid, we finally chose silicone oil 3 cSt (3 mm 2 s −1 ) (Triest and Alemany, 2014). The density of this fluid can balance the ice pressure (930 kg m –3 at 0°C and 970 kg m –3 at –40°C); its freezing point is around −120°C; and its kinetic viscosity is reasonably low (3 mm 2 s −1 at 25°C) even though this value rapidly increases below −30°C (12mm 2 s −1 at –55°C, which is three times greater than with the usual mixture of kerosene D40 with hydrochlorofluorocarbon HCFC-141b).…”
Section: The Subglacior Probe Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The density-viscosity tests (Talalay, 2007;Triest and Alemany, 2014;Xu et al, 2014) demonstrated that only a small number of DSOs and FAEs meet the ice-drilling requirements. Furthermore, some of the physicochemical properties of these liquids were unknown and require further clarification before conducting practical experiments in the test boreholes.…”
Section: Introductionmentioning
confidence: 98%
“…Although there are several DSOs, the low-viscosity grades (b 5 mm 2 s −1 ) of silicones (e.g., KF96-1,5cs and KF96-2,0cs) are the closest match to the requirements for a drilling fluid (Triest and Alemany, 2014). Some of DSOs, namely PMX200 from Dow Xiameter, have exposure limits; however, most of DSOs have no specifications on the air contamination levels.…”
Section: Introductionmentioning
confidence: 98%